Unveiling the Drivers of Customer Satisfaction in the Hotel Industry - Aryal, Mani Ram; Dangol, Sunita; Pradhan, Kohishma (Nepalese Journal of Business and Management Studies, 2023)
Customer satisfaction represents the foremost determinant in fulfilling the requirements of consumers, with factors conducive to achieving consumer contentment encompassing service quality and pricing. Certainly, the hotel sector has emerged as a worldwide phenomenon, featuring a diverse array of customers and providers spanning the globe. els and related services have become an integral part of many people's lifestyles. Delivering top-notch services is crucial for attracting and retaining customers, while ensuring fairness in pricing enhances this appeal. Therefore, the current study aims to examine the influence of service quality and price fairness on the satisfaction of customers. For this quantitative study, data were collected from 92 hotel visitors in the Thamel area. The research design used in the study consists of descriptive, relational and casual research designs. The data were analysed using SPSS along with various tools, such as the mean, median, standard deviation, correlation, regression, etc. The study revealed that both service quality and price fairness positively impact customer satisfaction in this context. This finding underscores the importance for hotels to focus on both delivering excellent service and ensuring fairness in pricing to enhance overall customer satisfaction and, potentially, loyalty.